Consumer responses to corporate social irresponsibility: The role of moral emotions, evaluations, and social cognitions - Xie, Chunyan; Bagozzi, Richard P. (Psychology & marketing, 2019)
We investigate the mediating roles of moral emotions and attitudes between perceptions of corporate irresponsible actions, on the one hand, and consumer responses, on the other hand, and further examine their contingencies based on consumer social cognitions. Our findings show that, for corporate transgressions, multiple social cognitions (moral identity, relational and collective self‐concepts, and affective empathy) moderate the elicitation of negative moral emotions (contempt and anger) and overall evaluations (attitudes), which, in turn, lead to negative responses toward the company (negative word of mouth, complaint behaviors, and boycotting). Our study adds to extant research on corporate social irresponsibility by examining three generic reactions people have toward corporate social irresponsibility and demonstrating important boundary conditions. In addition, hypotheses are tested on a sample of adult consumers. Implications for communication by firms are considered.